Pelatihan Desain Pembelajaran Interaktif Berbasis Artificial Intelligence untuk Meningkatkan Efektivitas Pembelajaran Digital Di MI Muhammadiyah Tambaksari Kabupaten Blora - Yeri Utami; Gita Permatasari, Kristina; Bayu Gumilar, Eko; Dwi Prastiawan, Muhammad; Amalia Putri, Fika; Mega Oktaviani, Tiara (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
The development of digital technology has brought significant changes in the field of education, particularly in the design and delivery of learning materials. Madrasah Ibtidaiyah (MI) Muhammadiyah Tambaksari in Blora Regency, as a faith-based primary educational institution, faces challenges in utilizing Artificial Intelligence (AI) technology in teaching and learning activities due to limited understanding and skills among teachers. Through a community service program, training on interactive learning design based on AI was provided to 12 teachers at MI Muhammadiyah Tambaksari. The training consisted of four sessions covering an introduction to AI, training on interactive learning design, the use of AI-based digital applications, as well as evaluation and feedback. Evaluation results showed a significant improvement in teacher competencies, with an average post-test score of 88 compared to a pre-test score of 53. Classroom implementation demonstrated a positive student response to AI-based learning, with 95% of students expressing interest in learning again using similar media. The outcomes of this program not only enhanced teachers’ abilities in designing engaging and adaptive digital learning, but also had a positive impact on students' motivation and engagement in the learning process.